Phonostylistic Tendencies with Reference to the Presentation of Brexit in the Bagehot Rubric of the Economist - Dimitrov, Georgi (Research Papers, 2020)
This paper aims at outlining phonostylistic tendencies with reference to the presentation of Brexit in the Bagehot rubric of The Economist from 2017 to mid-2019. The introductory section offers a theoretical framework according to which sound symbolism is important and indispensable part of language. The next section presents an analysis of the empirical data. The concluding section summarises the empirical results and makes predictions regarding the phonostylistic presentation of Brexit until Britain leaves the EU.